Localized orbital description of ideal vacancies in ZnS, ZnSe and Te - (:unkn) unknown (My University, 2000)
Kübik ZnS, ZnSe ve ZnTe kristallerinin içindeki ideal boşluklar yerel yörünge metodu (YYM) ile çalışılmıştır. Bant yapıları, etkin Gauss orbitallerinin idealize edilmiş görünen potansiyellerle birlikte kullanılmasıyla hesaplanmıştır. Hesaplamalar, valans ve alt iletken bantları ve katının durum yoğunlukları için deneysel verilerle iyi bir uyum içindedir. Teknolojik önemdeki kübik Zn-bazlı yarı iletkenlerdeki bozukluk durumları için (YYM) ilk olarak uygulanmıştır. (YYM)'nin pratik yararlan ve katının bant yapısının doğru parametrizasyonunun, bozukluk hesaplamalarındaki önemi vurgulanmıştır.

The ideal vacancies in cubic ZnS, ZnSe and ZnTe crystals are studied by the localized orbital method (LOM). The band structures are calculated using an efficient basis set of Gaussian orbitale along with the optimized pseudopotentials. The calculations are in good agreement with experimental data of valence and lower conduction bands and bulk densities of states. This is the first applicatiön of (LOM) to defect states of technologically important cubic Zn-based semiconductors. The practical utility of LOM and the importance of an accurate bulk band structure parametrization in defect calculations have been emphasized.
ZnS, ZnSe ve ZnTe içindeki ideal boşlukların yerel yörünge tarifleri